Perbedaan Sifat Biologi Tanah pada Beberapa Tipe Penggunaan Lahan di Tanah Andisol, Inceptisol, dan Vertisol - SARIDEVI, GUSTI AGUNG AYU RATIH; ATMAJA, I WAYAN DANA; MEGA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Differences in the nature of Soil Biology in Several Types of Land Use Land Andisol, Inceptisol, and Vertisol The aim of this research is to find out the difference of biological properties of soil on several types of land use in Andisol, Inceptisol, and Vertisol soil. The research was conducted on November 2012 until January 2013, starting from sample collection preparation up to soil analysis. Soil sample collection was conducted at Batunya Village (Andisol soil), Kuwum Village (Inceptisol soil), and Pererenan Village (Vertisol soil). Soil sample was analyzed at Soil Laboratory, Faculty of Agriculture University of Udayana. The design used was Randomized Block Design (RAK) of nested pattern with 2 factors, that was soil type factor (T) consisted of T a (Andisol Soil), T i (Inceptisol Soil), and T v (Vertisol Soil), and second factor of land use type (L) consisted of L s ( irrigated land use types with rice ), L c ( mixed farming ), and L j ( irrigated land use types with corn ). The parameters observed in this research among others were total bacterial population, total fungi population, respiration, C-organic content, N-total content, the ratio of C/N and pH. Andisol soil with land use type of mixed farmland (T a L c ) has the highest total of bacterial population, at 6,26 x 10 8 spk g -1 of soil, highest total fungi population and highest respiration. Inceptisol soil with land use type of mixed farmland (T i L c ) has the highest total bacterial population, at 6,62 x 10 8 spk g -1 of soil, highest total fungi population and highest respiration. Vertisol soil with land use type of mixed farmland (T v L c ) has the highest total bacterial population, at 6,07 x 10 8 spk g -1 of soil, highest total fungi population and highest respiration. Andisol, Inceptisol, and Vertisol with three types of land use that are rice field, mixed farmland, and corn field have different biological properties. The type of land use of mixed farmland has biological properties of soil higher than other types of land use. Key words: Type of soil, Type of land use, and Biological properties of soil
Keywords: Type of soil; Type of land use; Biological properties of soil